Respuesta :

Answer:

y+4 = -3(x+1)

Step-by-step explanation:

We have a point and a slope, so we can use point slope form to write and equation

y-y1 = m(x-x1) where m is the slope and (x1,y1) is the point

y - -4 = -3(x--1)

y+4 = -3(x+1)

This is in point slope form

Answer:

[tex]\boxed{y+4 = -3(x+1)}[/tex]

Step-by-step explanation:

Slope = m = -3

x₁ = -1

y₁ = -4

Putting in point slope form:

[tex]y - y_{1} = m(x-x_{1})[/tex]

=> [tex]y - (-4) = -3(x - (-1))[/tex]

=> [tex]y+4 = -3(x+1)[/tex]